DINAMIKA KEDUDUKAN TAP MPR DI DALAM HIERARKI PERATURAN PERUNDANG-UNDANGAN - martha riananda (Fiat Justisia: Jurnal Ilmu Hukum, 2014)
People's Consultative Assembly (MPR) decree dynamics position in the hierarchy of legislation and as the legislation arising drowned in accordance political developments and laws and regulations governing the order of legislation. Keywords: Position, People's Consultative Assembly (MPR) and the hierarchy of legislation